Finish machining-induced surface roughness, microhardness and XRD analysis of selective laser melted Inconel 718 alloy - KAYNAK, YUSUF (ELSEVIER SCIENCE BV, 2018)
Selective laser melting (SLM) is one of the most commonly used additive manufacturing (AM) techniques to manufacture metal components; however, during building process partially melted powders and/or pores on the outer surface of metallic parts results in very high surface roughness and eventually poor surface quality of components manufactured by selective laser melting. Thus, post-processing is needed to improve surface quality and also control subsurface characteristics. Hence, this study presents the effects of finish machining process on surface integrity characteristics including surface roughness, microhardness and XRD analysis of selective laser melted (SLMed) Inconel 718 alloy. In machining process of SLMed Inconel 718 alloy, the effect feed rate on measured outputs was also examined. Besides, the role of cold air on surface integrity characteristics was also presented in this study. This study reveals that arithmetic average surface roughness of as-built SLMed Inconel 718 can be lowered more than 90% with finish machining post processing operation. Increased feed rate results in work hardening on the surface and subsurface and eventually microhardness of surface and subsurface increases notably as compared to as-built SLMed Inconel. Finish machining process deeply influences XRD patterns of SLMed Inconel 718 alloy. (C) 2018 The Authors. Published by Elsevier Ltd.
Keywords: Additive Manufacturing; Selective Laser Melting; Finish Machining; Inconel 718 alloy; Surface integrity; IMPROVEMENT; BEHAVIOR